Weight regain among women after metabolic and bariatric surgery: a qualitative study in Brazil - Carvalho Jr.,Ataliba de (2014)
INTRODUCTION: Due to the increased number of bariatric surgeries over the years, aspects contributing or hindering the achievement of outcomes, among them weight regain, have acquired increased significance. Psychological factors directly influence on this unwanted situation, but there are few studies and controversies about the degree of participation of these factors. We propose a qualitative investigation to analyze the meanings of weight regain after surgery among women and how these factors influence this outcome.METHOD: This study uses the clinical-qualitative method, by means of a semi-structured interview with open questions in an intentional sample, closed by saturation, with eight women who underwent surgery at the Bariatric Surgery Outpatient Clinic of Hospital das Clínicas, Universidade Estadual de Campinas (UNICAMP), in the state of São Paulo, Brazil.RESULTS: A feeling of defeat and failure emerges with weight regain, which contributes to social isolation; there is no regret, but gratitude for the surgery; among patients, there is a sense of feeling rejected greater than a rejection that actually exists.CONCLUSION: We found out the need for further qualitative studies that help the health team to better understand the dynamic psychological factors involved in the meaning of weight regain after bariatric surgery among women, in order to adopt appropriate conducts to deal with this problem.